Estimation of Alexithymia by Body Fat Ratio in Adolescents with Overweight and Obesity - Nazan Kaymaz; Hande Şirin; Mehmet Erdem Uzun; Özlem Kara (İstanbul Medical Journal)
Introduction: This study investigated the association between adiposity and alexithymia risk among adolescents with overweight (OW) and obesity (OB). Methods: In this cross-sectional study, adolescents who are OW or obese completed a sociodemographic questionnaire and the Toronto Alexithymia Scale (TAS). Anthropometric measurements-including weight, height, waist, and hip circumference-were collected, and body fat percentage was determined via bioelectrical impedance analysis. Participants were categorized into two groups based on the presence or absence of alexithymia, and statistical comparisons were conducted using appropriate parametric and non-parametric tests. Receiver operating characteristic (ROC) analysis was performed to evaluate the predictive value of adiposity indices. Results: The study included 105 adolescents (69 females, 36 males). Alexithymia was present in 49.5% of participants, with a significantly higher prevalence among females (77%). Total TAS scores were positively correlated with body fat percentage and waist-to-height ratio (WHtR). A body fat percentage above 35.5% and WHtR over 0.61 showed moderate diagnostic performance, with respective sensitivities of 71.15% and 75%, and specificities of 54.72% and 65.51%. The area under the ROC curve was 0.632 [95% confidence interval (CI): 0.533-0.724] for body fat and 0.622 (95% CI: 0.522-0.715) for WHtR. Conclusion: Among adolescents with OW or OB, those with a body fat percentage over 35.5% or a WHtR above 0.61-particularly females-may have an increased risk of alexithymia. These findings underscore the need for integrating emotional and metabolic assessments in the clinical care of this population.